SISTEM INFORMASI DESA PANEKAN DAN KOMUNITAS WARGANYA DI JAKARTA - Francisca Francisca; Wasino wasino; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
At this time, Information and Communication Technology develops very rapidly. Many people began to use the Internet as a primary source of information. Besides being easier and faster, the information obtained from the Internet is usually more up to date. Panekan is a village in the district Eromoko, Wonogiri, Central Java. Panekan village has not been published due to lack of information that can be searched on the Internet, as well as community residents Panekan village located in Jakarta, so the Panekan village website and His community located in Jakarta is indispensable in order to facilitate communication between village residents and community Panekan. The methodology used in the website designing Information Systems and Communities Panekan Rural Citizens in Jakarta is the method of System Development Life Cycle (SDLC). In website designing Information Systems and Communities Panekan Village Citizens in Jakarta data collection is done by several methods, methods of data collection among others:a. Literature review. Author reading and studying books, journals or scientific papers related to a website designed.b. Observation The author conducted observations to obtain data on Panekan village. Observations using secondary data. The programming language using HTML, PHP, CSS, MySQL database, and the XAMPP Control Panel as a server at localhost. The Collections of data through interviews and observation in Panekan village. K3P-Panekan website has been created so that public can get information about Panekan village and its community, and website K3P – Panekan is a medium of communication between Panekan villagers and its community.